Liquidity Management and Real Estate Performance in Nigeria - Isaac Ayomide ISAYINKA; Ochei Ailemen IKPEFAN; David Oluwatobi FASHEYITAN (Communications of International Proceedings, 2022)
The rising cost of building materials and the deficit in demand and supply of housing are issues yet to be resolved in Nigeria. This study examined liquidity management implications on real estate performance in Nigeria using secondary data with yearly panel data characteristics from 2015 to 2019. A model was analyzed using the fixed-effect statistical approach to meet the study's goal. The current ratio, quick ratio, inflation rate, and interest rate were the explanatory variables explaining their various implications on real estate return on assets which proxy its performance in Nigeria. Data were obtained from 5 different real estate companies in Nigeria: Arbico Plc, Julius Berger, Smart Products Nigeria Plc, Union home, and Updc Property Dev. From the empirical findings of this study, the current ratio, inflation rate, and interest rate positively impact real estate performance. In contrast, the quick ratio has a negative implication on real estate performance in Nigeria. Due to the empirical findings, the study recommends that the Central Bank of Nigeria create an incentive for banks lending to the real estate sector. This will encourage banks to lend more to individuals and firms investing in the real estate sector. Also, the price level of the Nigerian economy should be stabilized as the existence of a high inflation rate will cause Nigerians to be unable to afford houses which will, in turn, decrease the performance of real estate in Nigeria.
Keywords: Real Estate; Liquidity Management; Current ratio; Quick ratio